Cinta di Era Digital: Mengungkap Mencari Pasangan di Waplog melalui Perspektif Fenomenologi Alfred Schutz - Tati Hilayati; Mayasari; Tri Widya Budhiharti (KOMVERSAL, 2025)
This research aims to understand the phenomenon of looking for a partner on the online dating application Waplog, through Alfred Schurtz's phenomenological approach. This research focuses on the motives, meanings and communication experiences experienced by users of the online dating application Waplog in their efforts to find a partner. Qualitative methods with a phenomenological approach were used to explore the subjective experiences of informants selected purposively. Data collected through in-depth interviews and analyzed using phenomenological interpretation. The research results show that the motives of Waplog application users vary from the need for social interaction to efforts to forget painful past experiences. The meanings formed in this application also differ depending on the user's background and expectations, be it for a friend to talk to, starting a new relationship, having the courage to express feelings, or starting a more serious relationship. The communication experience that occurs also reflects a unique social experience, where online dating users on the Waplog application have meaning and management in virtual interactions. This research provides new insights into how individuals interpret their experiences in the digital world in the context of finding a partner. These findings also highlight that technology shapes social interaction patterns and the dynamics of interpersonal relationships in the digital era.